2010
DOI: 10.1002/cphc.200901020
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Study of the Reaction between Ni+ and H2S

Abstract: The reaction between the Ni(+) cation and H(2)S is studied by considering both the doublet ground state and the lowest-lying quartet state. For the doublet state the reaction is endothermic, whereas it is exothermic for the quartet state. Both CCSD(T)//B3LYP and B3LYP levels of theory, combined with the triple-zeta quality TZVP++G(3df,2p), predict that there are three spin crossings along the characterized reaction path. The first one is located after the first transition state, and the second and third ones b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…It is observed that only the doublet state of HPdOH + has a T1-diagnostic value larger than the recommended threshold, and that its quartet state lies on the mark. We have recalculated both states with a multiconfigurational CASSCF-A C H T U N G T R E N N U N G (17,12) wave function. Notice that the selected active space contains all the valence electrons and all the valence orbitals resulting from the atomic configurations of the Pd 4d 9,8 5 s 0,1 , O 2s 2 2p 4 and H 1 s 1 .…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 4 more Smart Citations
“…It is observed that only the doublet state of HPdOH + has a T1-diagnostic value larger than the recommended threshold, and that its quartet state lies on the mark. We have recalculated both states with a multiconfigurational CASSCF-A C H T U N G T R E N N U N G (17,12) wave function. Notice that the selected active space contains all the valence electrons and all the valence orbitals resulting from the atomic configurations of the Pd 4d 9,8 5 s 0,1 , O 2s 2 2p 4 and H 1 s 1 .…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Therefore, the quartet spin state can be long‐lived enough to undergo reactions with CH 4 and also with the O 2 molecule 30. On the other hand, the doublet spin state undergoes rapid rearrangement to the nonreactive C 2 v symmetric Ni + ⋅⋅⋅ OH 2 complex, as demonstrated by using simple quantum molecular dynamics calculations 12…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations